The Effects of Brand Loyalty on Competitive Price Promotional Strategies - Raju, Jagmohan S.; Srinivasan, V.; Lal, Rajiv (Management Science, 1990)
This paper analyzes the role played by brand loyalty in determining optimal price promotional strategies used by firms in a competitive setting. (Loyalty is operationalized as the minimum price differential needed before consumers who prefer one brand switch to another brand.) Our objective is to examine how loyalties toward the competing brands influence whether or not firms would use price promotions in a product category. We also examine how loyalty differences lead to variations in the depth and frequency with which price discounts are offered across brands in the same product category. The analysis predicts that a brand's likelihood of using price promotions increases with an increase in the number of competing brands in a product category. In the context of a market in which a brand with a large brand loyalty competes with a brand with a low brand loyalty, it is shown that in equilibrium, the stronger brand (i.e., the brand with the larger loyalty) promotes less frequently than the weaker brand. The results suggest that the weaker brand gains more from price promotions. The analysis helps us understand discounting patterns in markets where store brands, weak national brands, or newly introduced national brands compete against strong, well known, national brands. The findings are based on the unique perfect equilibrium in a finitely repeated game. The predictions of the model are compared with the data on 27 different product categories. The data are consistent with the main findings of the model.